LITERATURE STUDY OF THE EFFECT ON DOPING COMPONENT ON THE CE-TI OXIDE CATALYST FOR FLUE GAS DENITRATION WITH NH3-SCR - Rias Becik Sinawang; Cucuk Evi Lusiani (DISTILAT: JURNAL TEKNOLOGI SEPARASI, 2022)
The Ce-Ti oxide catalyst is viewed as an innovation for the reduction of nitrogen oxide (NOx) and owns outstanding activity in ammonia-selective catalytic reduction (NH3-SCR) that became the most used denitration reaction in industry. In the flue gas, there will be many substances that inhibit the catalytic activity. Therefore, adding some components to the Ce-Ti oxide catalyst can be a solution. The aim of this literature study is to analyze the effect of doping components (Fe, Zr, Cu, K) on Ce-Ti oxide catalyst in the NH3-SCR reaction. Several theories and data methods were collected by comparing data based on catalytic activity and characterization of the catalysts. The activity of the catalyst was obtained by calculating the NOx conversion. The characterization of the catalysts was detected by BET, H2-TPR, NH3-TPD, and XPS. The analysis based on the literature study exhibited a catalyst with the best activities, structures, and properties required to successfully reduce NOx. The results indicate that the effect on doping components of Fe, Zr, and Cu can enhance the characteristics and protect the reduction ability, whilst the doping of K decreases surface acidity and reducibility on Ce-Ti oxide catalyst.